Analisis Kepuasan Mahasiswa Ditinjau dari Kualitas Pelayanan, Kualitas Pembelajaran Dimoderasi Oleh Biaya Pendidikan - Mas Intan Purba; Ani Murwani Muhar; Wistira Maulana (Universitas Harapan Medan, 2022)
This research was done by the social science faculty at Universitas Panca Budi Medan with the aim of research to know the influence of service quality and learning quality toward student satisfaction moderated by education cost. The type of research used was qualitative research. The study population was regular and executive students in the social science faculty of Universitas Panca Budi Medan as many as 2,580 students in 2018. Sampling using random sampling with a sample size of 100 respondents. Sources of data using primary data with data retrieval were surveyed. Data analysis techniques used multiple linear regression, MRA (Moderating Regression Analysis) analysis, classical assumption test, and hypothesis test. Based on the results of the research conducted, it could be shown that the quality of service and the quality of learning partially significantly affected student satisfaction in a study on the social science faculty in Universitas Panca Budi Medan. The quality of service and the quality of learning simultaneously have a significant effect on the students' satisfaction of study on the social science faculty in Universitas Panca Budi Medan. The quality of service and quality of learning has a moderate relationship with student satisfaction in the faculty of social science of Panca Budi University Medan. Meanwhile, the satisfaction of students of the social science faculty could be explained by the quality of service and the quality of learning in Universitas Panca Budi Medan 23.2% and the rest 76.8% by others variables that did not examine.